Fertilizer and soil fertility potential in Ethiopia: Constraints and opportunities for enhancing the system - Zeleke, Gete; Agegnehu, Getachew; Abera, Dejene; Rashid, Shahidur (International Food Policy Research Institute, 2010)
This document is a summary report of the soil fertility and fertilizer value chain diagnostic work-one of eight reports across the agricultural system facilitated by the Bill & Melinda Gates Foundation and undertaken at the request of H.E. Prime Minister Meles Zenawi. Over 70 stakeholders, ranging from smallholder farmers and local Development Agents to the private sector and the Ministry of Agriculture and Rural Development, contributed to the report's findings and recommendations.